Conceptual development of resources discovery in the proposed hybrid P2P video streaming - Nanna Suryana, Herman (2007)
We present the design of a hybrid Peer-to-Peer (P2P) system for video streaming. In this paper, we address the availability, accessibility and lookup service of files. We use the advantages of server-client business model to search and retrieve the information. We implement the base ontology of video domain repository so that the final result may be different and provide more results from the keyword search. To provide the dynamic standby peer, we use checksum value as an indicator to search an identical content in the Peer-to-Peer network. We hypothesize that, by using server-client searching in Peer-to-Peer application, we can reduce the latency lookup services, path length, peer load and network traffic.